The heterologous expression and in vitro biochemical characterization of the Hsp70 escort protein 1 and mitochondrial Hsp70 partner proteins of the Trypanosoma brucei parasite and humans - Mahlalela, Maduma Ernst (Rhodes University, Faculty of Science, Biotechnology Innovation Centre)
The 70 kDa family of heat shock proteins (Hsp70) plays a central role in the maintenance of cellular proteostasis, with paralogues occurring in all the major compartments of the eukaryotic cell. Hsp70s act in conjunction with proteins known as co-chaperones, as part of the larger molecular chaperone network. In the mitochondrion, Hsp70 (mtHsp70) is responsible for the import of proteins synthesized in the cytosol, protein folding in the matrix and the maintenance of the iron-sulphur cluster. In human cells mtHsp70 (HSPA9) is also referred to as mortalin, as the knockdown of the protein leads to cell mortality. Trypanosoma brucei is the causative agent of sleeping sickness in humans and nagana in animals. In the T. brucei parasite there are three identical mtHsp70 (TbmtHsp70) proteins that are produced, forming part of the Hsp70 machinery that is essential for parasite survival. In humans, the levels of HSPA9 are often elevated in non-communicable diseases such as cancer and neurodegeneration. Despite their vital cellular roles, mtHsp70s are characteristically prone to self-aggregation. The binding of the Hsp70 escort protein (Hep1) is required to prevent the aggregation of mtHsp70 proteins, enabling the proteins to function. In many non-communicable diseases, mtHsp70 and other molecular chaperones such as heat shock protein 90 (Hsp90) are being investigated as potential drug targets. Existing anti-trypanosomal drugs for treating sleeping sickness are toxic, having adverse side effects that are potentially lethal. Investigations into Hsp70s, and other molecular chaperones, form part of the research into the discovery of novel and efficacious therapeutics. This is the first study to characterise Hep1 and investigate its partnership with mtHsp70 in T. brucei. The overall aim of this study was to comparatively assess the T. brucei and human mtHsp70/Hep1 partnerships. The putative T. brucei Hep1 (TbHep1) orthologue was analysed in silico, and it was found to possess a zinc finger domain consisting of anti-parallel Î²-sheets that are characteristic of canonical Hep1 proteins, whilst the N-terminal domain was unstructured. Based on sequence analysis, the regions outside of the zinc finger domains lacked conservation. Despite the lack of sequence conservation, the N- and C-terminal regions of TbHep1 shared segments of similarity with Hep1 orthologues of other kinetoplastid and trypanosomal orthologues. The same held true for the N- and C-termini of human Hep1 (HsHep1) when compared to other Hep1 orthologues of mammalian origin. Biochemical analysis revealed TbmtHsp70 and HSPA9 to be prone to self-aggregation, which was reduced by co-expression with TbHep1 and HsHep1, respectively. Recently Hep1 proteins have been determined to be present in the cytosol. In this study, TbHep1 and HsHep1 also interacted with the cytosolic Hsp70s, HSPA1A and TbHsp70, by preventing their thermally induced aggregation and stimulating their ATPase activities. TbHep1 and HsHep1 also suppressed the thermally induced aggregation of the model substrates malate dehydrogenase and citrate synthase, independently of Hsp70. To date, only two Hep1 orthologues, HsHep1 and LbHep1, have been found to function in a similar manner to a J-protein co-chaperone by stimulating the ATPase activities of their partner mtHsp70 proteins. In this study, TbHep1 stimulated the ATPase activity of TbmtHsp70. HsHep1 also stimulated the ATPase activity of TbmtHsp70. However, the mechanism of action still needs to be determined. This study also explored the potential of the Hep1 orthologues to be functionally activated by oxidative stress, which is prevalent in mitochondria. The abilities of TbHep1 and HsHep1 to reduce the thermally induced aggregation of malate dehydrogenase were enhanced under oxidative conditions. Disrupting the function of Hep1 has been found to eventually lead to cell death, and given the critical role played by mtHsp70 in the cell, this partnership could be exploited as a potential drug target. In conclusion, this study demonstrated that TbHep1 and HsHep1 functionally interact with mtHsp70s, whilst also possessing independent chaperone activities that are also potentially influenced by the environmental redox state.
Keywords: Hsp-70; Heat shock proteins; Molecular chaperones; African trypanosomiasis; Trypanosoma brucei; Kinetoplastida; Neglected tropical disease